The Digital Economy, Industry 4.0 and digital payment systems : impacts on international organizations - Mojžíš, Radek; Bolotov, Ilya; Hinčica, Vít; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This paper examines the emerging Digital Economy with relation to Industry 4.0 and digital payment technologies. An objective of the study is to present main trends in these segments and their impacts on international organizations. The first part focuses on general introduction to the Digital Economy and Industry 4.0. This includes description of fundamental terms, trends and connections to chosen European countries. The second part inspects current trends in digital payment systems, digital currencies and blockchain technology. The third part analyses and deduces impacts of new technologies on economy and international organizations regarding their management, strategies and social responsibilities. Conclusion summarizes main trends of digitization and their impacts on economy and international organizations.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses